Performance of Etest and Disk Diffusion for Detection of Ciprofloxacin and Levofloxacin Resistance in Salmonella enterica - Deak, Eszter (J Clin Microbiol, 2014)
We compared Etest and disk diffusion to broth microdilution for the detection of fluoroquinolone resistance in 135 typhoidal and nontyphoidal serovars of Salmonella. Categorical agreements for the ciprofloxacin and levofloxacin Etests were 89.6 and 83.7%, respectively. Disk diffusion categorical agreements were 88.2 and 93.3%, respectively. Only minor errors were observed.